Magnetism and anomalous apparently inverse Jahn-Teller effect in Sr2CrO4. (2nd September 2019) - Jeanneau, Justin; Toulemonde, Pierre; Remenyi, Gyorgy; Sulpice, André; Colin, Claire V.; Nassif, Vivian; Suard, Emmanuelle; Gay, Frederic; Weht, Ruben; Núñez-Regueiro, Manuel
Abstract: We have performed neutron diffraction measurements of tetragonal Sr2 CrO4 to study the crystallographic structure as a function of temperature and the magnetic properties developed below . We have measured the precise positions of the oxygen atoms of the CrO6 octahedra and observed that, with decreasing temperature, the octahedra pass from elongated to almost ideal, contradicting the intuitive idea of a Jahn-Teller effect. DFT calculations explain this apparent anomalous behaviour by establishing that energy level degeneracy only exists in a highly elongated octahedra. Our study agrees with the idea of a weak orbital ordering transition around 150 K followed by an itinerant antiferromagnetic ordering at 110 K with a wave vector determined both from neutron powder diffraction and theory.